2015
DOI: 10.4236/psych.2015.614190
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Incivility and Its Effects on Value Congruence, Recovery-Stress-State and the Intention to Quit

Abstract: Negative social interactions, such as workplace incivility, show a strong connection to work-related negative outcomes, such as exhaustion or intention to quit. Despite being aware of the important role of incivility in employees' working life, there is still a lack of research on moderators and mediators in the relationship of incivility and work-related outcomes. In the present study, the moderating roles of stress, recovery and value incongruence on the relationship of incivility with intention to quit are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…These results are in line with past research (Bakker et al, 2005;Jiménez, Dunkl, & Peißl, 2016) and the model of resources/recovery-stress balance, where recovered resources are able to reduce feelings of stress, which in turn raises JS and lowers the intention to quit the job.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with past research (Bakker et al, 2005;Jiménez, Dunkl, & Peißl, 2016) and the model of resources/recovery-stress balance, where recovered resources are able to reduce feelings of stress, which in turn raises JS and lowers the intention to quit the job.…”
Section: Discussionsupporting
confidence: 91%
“…The important role of resources/recovery becomes especially apparent if we include organizational outcomes such as intention to quit in the stress-recovery relationship. Research shows that resources/ recovery are negatively related to intention to quit, and this relationship is fully mediated by stress (Bakker, Demerouti, & Euwema, 2005;Jiménez, Dunkl, & Peißl, 2016). This result supports the assumption of the model of resources/ recovery-stress balance, where recovered resources potentially buffer negative effects of demands by reducing stress.…”
Section: Theoretical Backgroundsupporting
confidence: 75%
“…The shortcomings of the studies of the integration of elements of industry 4.0 and hence the lack of confidence in new procedures by the top management are already expected obstacles (Marik, 2016). Changes under these assumptions may increase the level of stress (Jim enez, Dunkl, Peißl, 2015;Jim enez, Dunkl, Stolz, 2015; Vlacsekov a, 2019) may have a negative effect on the perception of employee satisfaction. Creating suitable conditions for quality employees in key positions represents a reduction in the risk of their loss and a possible increase in loyalty to the company (Jigjiddorj et al, 2019).…”
Section: Verification Of Hypotheses and Discussion Of Research Resultsmentioning
confidence: 99%
“…In different studies in the literature (Cortina et al, 2001;Kanten, 2014;Selamat et al, 2019;Jiménez et al, 2015;Yuniasanti et al, 2019;Nazir et al, 2016;Liu et al, 2017;Rahim & Cosby, 2016) ) workplace incivility has been observed to positively affect the intention to leave. However, in the study conducted by Batga and Ceyhan (2019) on bank employees, it was seen that workplace incivility did not affect the intention to leave.…”
Section: Extended Abstractmentioning
confidence: 99%